Control of a Multimode Double-pendulum Overhead Crane System Using Input Shaping Controllers - Sharifah Yuslinda Syed Hussien; Hazriq Izzuan Jaafar; Rozaimi Ghazali; Liyana Ramli; Mohd Khairul Azizat Johari (Association for Scientific Computing Electronics and Engineering (ASCEE), 2024)
Indexed by Scopus